Liquid biopsy for cancer patients: Principles and practice. Issue 1 (2015) - Cree, Ian A.
Abstract: Liquid biopsy has the potential to provide information about cancers without invasive biopsy, using circulating biomarkers. These include proteins, RNA and DNA. They can be used in detection, diagnosis, monitoring and detection of recurrence. While protein-based tumour markers have been used in routine pathology for many years, the ability to detect mutations in circulating DNA is relatively new, and poised to enter clinical practice. A number of issues remain, and it is important that such markers are fully validated before they enter clinical practice. Evidence of clinical utility and cost effectiveness are major hurdles, but it is likely that the use of liquid biopsy in defined settings could benefit cancer patients substantially.